IVORIA (Innovative, Creative, Varied) Interactive Teaching Media Based on Canva to Improve Learning Outcomes in Indonesian Language Material Main Ideas and Vocabulary - Puspitasari, Putri; Yulianto, Sigit (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
Indonesian Language Learning in Elementary Schools still faces obstacles in delivering materials. The lack of interactive learning media in the learning process causes low student learning outcomes. This study aims to develop an interactive IVORIA teaching media using Canva to enhance learning outcomes in Indonesian, with a particular focus on the main idea and vocabulary material for fourth-grade elementary school students. The type of research used is Research and Development (R&D) with the ADDIE development model. The research subjects consisted of 18 elementary school students who participated in large-group tests, and a sample of 8 students was selected using a purposive sampling technique. Data collection techniques were observation, interviews, documentation, questionnaires, and tests (pretest and posttest). The data analysis techniques employed were the normality test (Shapiro-Wilk), t-test, and N-Gain test. The results of the feasibility analysis for the IVORIA interactive teaching media were categorized as very feasible, with percentages of 93% among media experts, 95% among material experts, 98% among teacher responses, and 94% among student responses. The results of the analysis of media effectiveness, conducted using a paired t-test, showed a significance value of 0.001, with an average pretest score of 54.72 and an average posttest score of 79.44. The N-Gain score obtained was 0.54, indicating a moderate category. The results of the study indicate that the Canva-based IVORIA interactive teaching media is very feasible and effective in improving the Indonesian language learning outcomes of fourth-grade students. The implications of implementing technology in learning can also increase student engagement and learning outcomes, making it a worthy integration in basic Education.